Genetic parameters for reproductive traits of VCN03 breed - Sang Van Le; Pham Duy Pham; Hong Son Trinh (Vietnam Journal of Science, Technology and Engineering, 2018)
This study was conducted in Thuy Phuong Pig Research Center (TPPRC), Vietnam to determine the genetic parameters of four reproductive traits including numbers born alive (NBA), litter birth weight (LBW), number of weaned pigs (NW) and litter weaning weight (LWW). The reproductive performance of 254 sows of VCN03 breed from four generations between 2010 and 2017 was collected and used in this study. Data from NBA, LBW, NW and LWW were subjected to repeated-measures of ANOVA in PROC MIXED in SAS with four reproductive traits and generations as fixed factors. Data from heritabilities and genetics and phenotypic correlations were plotted using the ASReml. It was concluded that the heritabilities of the four traits ranged from low to moderate, resulting from 0.134 to 0.267. The heritabilities of NBA, LWW, LBW and NW were 0.264, 0.267, 0.137 and 0.134, respectively. The genetic and phenotypic correlations among the four traits were moderate to high positive. The genetic correlations ranged from 0.467 to 0.991, with the highest estimate for the genetic correlation being between LBW and NW and the lowest estimate for the genetic correlation being between NBA and LWW. The genetic correlation between NBA and NW was 0.67, between NBA and LBW was 0.774, between LBW and LWW was 0.69 and between LWW and NW 0.51.